SPI, HR Competence, and SAP Affect Sidoarjo Regional Financial Report Quality: SPI, Kompetensi SDM, dan SAP Mempengaruhi Kualitas Laporan Keuangan Regional Sidoarjo - Oktavia, Rindy Wahyu; Hariyanto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The demand for public sector accountability necessitates high-quality financial reporting, particularly in local government units like the Regional Financial and Asset Management Agency (BPKAD). Specific Background: The reliability of these financial reports is heavily reliant on internal organizational factors, specifically the control mechanisms, human capital capacity, and compliance with accounting standards. Knowledge Gap: Prior research has shown inconsistent results regarding the simultaneous influence of these key factors on financial report quality, creating an empirical gap that needs validation in specific regional contexts. Aims: This quantitative survey research aims to determine the combined and individual influence of the Internal Control System (ICS), Human Resource (HR) Competence, and the Effectiveness of Government Accounting Standards (GAS) on the Quality of Financial Reports at BPKAD Sidoarjo Regency. Results: Employing multiple linear regression on a sample of 45 respondents, the study concludes that the ICS, HR Competence, and the Effectiveness of GAS all significantly and positively affect the quality of financial reports. Novelty: The finding confirms the critical and unified role of all three variables as primary drivers of financial reporting quality, contributing specific data from BPKAD Sidoarjo. Implications: BPKAD should prioritize continuous professional development for HR, reinforce the existing ICS, and ensure strict adherence to GAS to maintain high report quality. Highlights: Internal Control System positively and significantly affects financial report quality. Human Resource Competence shows a significant positive correlation with report quality. Effectiveness of Government Accounting Standards significantly determines report quality. Keywords: Internal Control System, HR Competence, Government Accounting Standards, Financial Report Quality, BPKAD